The Effect of Modern Javanese Music on Generation Z Sleep Quality - Sami Liaqat; Kasiyan (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Contemporary Javanese music, particularly Campursari, blends traditional gamelan instruments with modern genres such as pop, dangdut, and keroncong. This hybrid style has gained popularity among Millennials and Generation Z, who often perceive it as familiar, calming, and emotionally comforting. This study examines whether listening to contemporary Javanese music influences the sleep quality of Generation Z in Yogyakarta. A quantitative research approach was employed using a survey distributed through Google Forms to 50 participants aged 19–26 years. The questionnaire measured listening frequency, emotional responses to the music, and perceived sleep quality using a Likert scale. The collected data were analyzed using SPSS with descriptive statistics, including the Kolmogorov–Smirnov normality test, linear regression, and tests for heteroscedasticity and multicollinearity. The results indicate a positive relationship between listening to contemporary Javanese music and improved sleep quality. The familiar and emotionally soothing characteristics of Campursari appear to help listeners relax and reduce stress before sleep. These findings suggest that culturally rooted music may serve as a simple, non-pharmacological approach to supporting better sleep and emotional well-being among young adults..